Effects of dry-land strength and conditioning programs in age group swimmers - Amaro, Nuno (2017)
Context: Even though dry-land S&C training is a common practice in swimming, there are countless uncertainties over it effects in performance of age group swimmers. Objective: To investigate the effects of dry-land S&C programs in swimming performance of age group swimmers. Participants: A total of 21 male competitive swimmers (12.7±0.7 years) were randomly assigned to the Control Group (n=7) and experimental GR1 and GR2 (n=7 for each group). Intervention: Control group performed a 10-week training period of swim training alone, GR1 followed a 6-week dry-land S&C program based on sets/repetitions plus a 4-week swim training program alone and GR2 followed a 6-week dry-land S&C program focused on explosiveness, plus a 4-week program of swim training alone. Results: For the dry-land tests a time effect was observed between week 0 and week 6 for vertical jump (p<0.01) in both experimental groups, and for the GR2 ball throwing (p<0.01), with moderate-strong effect sizes. The time*group analyses showed that for performance in 50 m, differences were significant, with the GR2 presenting higher improvements than their counterparts (F=4.156; ƿ=0.007; η2=0.316) at week 10. Conclusions: The results suggest that 6 weeks of a complementary dry-land S&C training may lead to improvements in dry-land strength. Furthermore, a 4-week adaptation period was mandatory to achieve beneficial transfer for aquatic performance. Additional benefits may occur if coaches plan the dry-land S&C training focusing on explosiveness.